EDUCATING FOR FUTURE JOBS - Lizut, Jaonna; Marzano, Gilberto; Grewinski, Miroslaw (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In a relatively short time, information and communication technology (ICT) has spread worldwide, from defense to space to large industrial applications, and to the commercial, healthcare, entertainment, and educational sectors. As a consequence, experts argue that it is urgent and critical to prepare educational programs in order to re-train the current workforce. However, there are some key questions that are very relevant, since they concern crucial and challenging issues: 1) Which jobs have a future in the digital era? 2) How can education support the acquisition of new skills required by the new jobs?This article focuses on the above questions, and presents the main opportunities that the digital revolution offers for sustaining education for future jobs in a lifelong perspective.